Beauty and the Beast: The Ordinary City versus the Mediatised City—The Case of Cairo. (November 2019) - Hendawy, Mennatullah; Saeed, Ahmed
Which city is made visible to those who use public versus private means of transportation? This question triggered an investigation of two alternate routes between two points in the mega urban city of Cairo, Egypt. Combining critical visual methodologies with ethnographic methods, this photo essay reveals the simultaneous existence of two cities as experienced by different publics: the 'ordinary city' of those who use public transport, and the 'mediatised city' of the elite who use private transport. Through comic-style photo editing, the essay demonstrates how the city is organised to include or exclude certain kinds of commuters using their chosen modes of transport, based on affordability and economic class.